ANALISIS GAYA KEPEMIMPINAN SITUASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMKN 8 LUWU - Hamira Hamira; Besse Herlina; Ferawati Ferawati; Hasnawati Hasnawati; Asriani Asriani; Arya Suyanti (STKIP Pesisir Selatan, 2026)
This study aims to analyze the application of situational leadership styles by the principal in improving teacher performance at SMKN 8 Luwu. Leadership in schools plays a strategic role in guiding and motivating teachers to carry out their professional responsibilities effectively. Employing a quantitative approach with a descriptive correlational design, the study involved all teachers at SMKN 8 Luwu, totaling 40 respondents selected through total sampling. Data were collected using observation, interviews, and questionnaires based on a Likert scale measuring four dimensions of situational leadership: telling, selling, participating, and delegating. The data were analyzed using descriptive statistics and Pearson correlation. Results revealed that the most dominant leadership style applied by the principal was participating (35%), followed by selling (30%), telling (25%), and delegating (10%). Furthermore, the correlation analysis indicated a strong and positive relationship between situational leadership and teacher performance, with a correlation coefficient of 0.70. These findings highlight that flexible and adaptive leadership styles significantly contribute to enhancing teacher performance in vocational education settings. The novelty of this research lies in mapping situational leadership styles according to teachers’ readiness and independence across different vocational programs. The study provides theoretical contributions to educational leadership research and practical implications for principals to adopt adaptive leadership strategies that foster a conducive work environment and improve the quality of teaching and learning.